Para uma periodização da história do jornalismo em Portugal - Sousa, Jorge Pedro (2021)
Periodization helps to rationally systematize historical phenomena, grouping them according to common denominators. It is both an instrument and a synthesis of historical knowledge, since it allows for the establishment of chronological stages that facilitate the understanding of historical development, marking continuities and ruptures (Rama, 1968; Kula, 1973; Gutierrez Espada, 1995; Pizarroso Quintero, 1999; Román Portas, 2000; Galindo Arranz, 2004; Godoy, 2008). However, it is a problematic interpretive intellectual exercise, since, even when founded on evidence, it never entirely sticks to material historical reality (Castro Ibaseta, 1999; Daly, 2009; Hayot, 2011). Considering, despite the limits, the usefulness of periodization for the understanding of historical phenomena, the present study aimed to establish a periodization for the history of Portuguese journalism, considering journalism as a communicative phenomenon, but from a historical perspective (Gómez Mompart, 1995). Although there are attempts to periodize the history of the Portuguese press until the end of the Monarchy (Tengarrinha, 1965, 1989, 2013; Sousa, 2017a), between 1968 and 2004 (Faustino, 2004), and of the Portuguese illustrated magazines until 1918 (Sousa, 2017b), as well as an attempt to periodize the history of the Portuguese press according to political regimes (Sousa, Lima, Hohlfeldt & Barbosa, eds, 2017), which is one of the ways to periodize the history of communication (Román Portas, 2000), a periodization of the history of journalism in Portugal has never been outlined. Being an interpretative exercise, the methodology of periodization of the history of Portuguese journalism was based on the rational grouping of historical phenomena over time, pointing out evident and verifiable continuities and ruptures in historical evolution. The following periodization is proposed for the history of Portuguese journalism: 1) Artisanal news press(from the late 16th century to 1730); 2) Segmentation of the press and dominance of the informative artisanal press (1730-1820); 3) Dominance of the political artisanal press (1820-1834); 4) Segmented pre-industrial press (1834-1864); 5) Segmented industrial press and development of mass news dailies (1864-1934); 6) Media segmentation of journalism (1934-1995), with three phases: (a) Censored machines; (b) Revolutionary disruption; (c) Liberalization; 7) Convergence and fusion (1995 to the present).